Europe and the global information society. Recommendation to the European Council. Brussels 1994. Building the Information Wigtvays to re-enginecr Europe - a message front industńals users. ERT (European Round Table). Brussels 1994. - Januszkiewicz, Franciszek (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
Recenzje i sprawozdania z książek